Monitoring muscle oxygenation after eccentric exercise-induced muscle damage using near-infrared spectroscopy - Ahmadi, S.; Sinclair, P. J.; Foroughi, N.; Davis, G. M. (Applied Physiology, Nutrition, and Metabolism, 2008)
Eccentric exercise (EE), a common type of muscular activity whereby muscles lengthen and contract simultaneously, is associated with higher levels of force but may also evoke muscle damage. We investigated the hypothesis that unaccustomed EE might impair muscle oxygenation and muscle blood flow in healthy adults. Ten healthy males performed a bout of 70 maximal eccentric contractions of the elbow flexors. Before and after EE on day 1 and over the next 6 days, maximum voluntary isometric torque (MVT), serum creatine kinase (CK), and the changes in muscle oxygen saturation, blood flow, and oxygen uptake (using near-infrared spectroscopy) within the biceps brachii were assessed. MVT decreased, whereas muscle soreness and CK increased after EE (p < 0.05). Mean resting oxygen saturation increased by 22% after acute EE, and remained elevated by 5%-9% for the following 6 days. During isometric contractions, significant decreases were observed in oxygen desaturation and re-saturation kinetics after EE and these declines were also significantly prevalent over the following 6 days. Both muscle blood flow and oxygen uptake increased significantly after acute EE, but recovered on the next day. This study revealed some prolonged alterations in muscle oxygenation at rest and during exercise after EE, which might be due to a decrease in muscle oxygen consumption, an increase in oxygen delivery, and (or) a combination of both. However, both oxygen consumption and blood flow recovered within 24 h after the eccentric exercise session, and therefore, the reason(s) for the changes in tissue oxygen saturation remain unknown.